OC-024 Development and validation of a novel capture-fusion model for HCV replication. (28th May 2012) - Cunningham, M E; Javaid, A; Waters, J A; Foster, G R
Abstract : Introduction: HCV replicates poorly in vitro, so testing of novel antiviral therapies currently relies on modified viral replicons, based on genotype (G)1, or the G2 JFH-1 virus. A model allowing patient virions to be cultured would facilitate drug discovery and allow direct sensitivity testing. Here we describe the development of a novel HCV replication assay, its validation using the antiviral agents alisporivir and telaprevir and its value in identifying responses to interferon and ribavirin. Methods: CD14 (+) monocytes derived from patients with chronic HCV infection, or pre-stimulated THP-1 cells infected with serum from G1 and G3 HCV infected donors, were fused with HuH7 cells and treated with antiviral agents at various concentrations. The fused cells were maintained in tissue culture for up to 5 days, before extraction of HCV RNA and quantification by PCR. p Values were derived using the Mann–Whitney U test for comparison of non-parametric data. Results are expressed as mean±SEM. Results: Replicating HCV from patients infected with diverse genotypes could be successfully transferred to HuH7 cells using the monocyte "capture-fusion" approach. RNA increased fivefold in fused cells and viral protein production as well as viral release could be demonstrated, confirming the presence of complete viral replication cycles in this new model. Treatment of G1 and G3 fused/infected Huh7 cells with escalating concentrations of alisporivir showed greater drug efficacy in cells infected with G3 than G1 (IC50 0.026±0.008 μM vs 0.109±0.02 μM, p=0.0286). Conversely, telaprevir showed greater efficacy in fused/infected cells with G1 than fused/infected cells with G3 HCV. Treatment with 0.1 μM telaprevir, which approximates its IC50 in replicon cells, resulted in a reduction of HCV RNA by 66.15±10.43% in G1 cells vs 21.56±3.16% in G3 infected cells (p=0.016). We examined sensitivity to interferon and ribavirin in samples from patients who did (N=3), or did not (N=4), respond to therapy. We found no significant difference in the viral sensitivity, suggesting that for interferon based therapies host factors play a more important role than virological response. Conclusion: These data confirm the value of a capture-fusion model for HCV replication in studying the replication of patient-derived HCV and demonstrate that for interferon and ribavirin based treatments, host factors dominate the response. However viral response determines the clinical response to direct acting anti-viral agents. This technique may be useful in identifying the most appropriate treatment strategies for patients with HCV planning therapy with the new direct acting antiviral agents. Competing interests: M Cunningham: None declared, A Javaid: None declared, J Waters: None declared, G Foster grant/research support from: Roche, Janssen, Tibotec, Novartis, Consultant for: Abbott, BI, BMS, Chughai, Janssen, Merck, Novartis, Roche, Tibotec.